Blood pressure control in primary care patients with arterial hypertension: analysing the Hypertension Register data - O. M. Posnenkova; A. P. Kiselev; V. I. Gridnev; V. A. Schwartz; P. Ya. Dovgalevskyi; E. V. Oshchepkova (Кардиоваскулярная терапия и профилактика, 2012)
Aim. (1) To investigate clinical characteristics of primary care patients with arterial hypertension (AH), according to the achievement of target blood pressure (BP) levels; (2) to assess the effectiveness of therapeutic measures aimed at achieving target BP and maintaining its long-term control. Material and methods. This retrospective analysis included the data from ambulatory medical records of 5558 AH patients, who attended primary care centres in 2007. Clinical characteristics were compared in patients with achieved vs. non-achieved target BP levels. According to the national AH guidelines (2004), the completeness of examination, pharmaceutical therapy tactics, and frequency of the follow-up were assessed in both groups. Results. Based on the 2007 data, target BP levels were maintained in 28% of AH patients. Mean BP level was 144/87 mm Hg. Patients with optimal BP levels, compared to their peers with inadequate BP control, had significantly (p<0,001) higher prevalence of angina pectoris (40,4% vs. 30,1%, respectively) or previous myocardial infarction (19,4% vs. 8,4%), as well as higher frequency of lipid profile assessment, creatinine measurement, and echocardiography. Mean number of prescribed antihypertensive medications was 2,08 vs. 1,60, respectively. Mean number of clinical visits per year was 4,07 vs. 2,99, while mean interval between the visits reached 72,3 vs. 62,7 days, respectively. Regardless of the target BP achievement, the quality of diagnostic and therapeutic management did not comply with the recommended standards. Conclusion. Patients with optimal BP control were characterised by a more severe clinical course, as well as by a wider scope and higher frequency of diagnostic and therapeutic procedures. At the primary care level, the quality of AH diagnostics and treatment did not comply with the recommended standards; therefore, mean BP levels in the AH Register sample were higher than the target ones.